Multislice CT angiography in cardiac imaging: prospective ECG-gating or retrospective ECG-gating? - Sun, Z (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, Malaysia, 2010)
With the advent of multislice CT more than a decade ago, multislice CT angiography has demonstrated a huge potential in the less invasive imaging of cardiovascular disease, especially in the diagnosis of coronary artery disease. The diagnostic accuracy of multislice CT angiography has been significantly augmented with the rapid technical developments ranging from the initial 4-slice, to the current 64-slice and 256 and 320-slice CT scanners. This is mainly demonstrated by the improved spatial and temporal resolution when compared to the earlier type of CT scanners. Traditionally, multislice CT angiography is acquired with retrospective ECG-gating with acquisition of volume data at the expense of increased radiation dose, since data is acquired at the entire cardiac cycle, although not all of them are used for postprocessing or reconstructions. Recently, there is an increasing trend of utilising prospective ECG-gating in cardiac imaging with latest multislice CT scanners (64 or more slices) with significant reduction of radiation dose when compared to retrospective ECG-gating method. However, there is some debate as to the diagnostic value of prospective ECG-gating in the diagnosis of coronary artery disease, despite its attractive ability to reduce radiation dose. This article will review the performance of retrospective ECG-gating in the diagnostic value of coronary artery disease, highlight the potential applications of prospective ECG-gating, and explore the future directions of multislice CT angiography in cardiac imaging.